2022
DOI: 10.3390/children9030329
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Vitamin D Level and Lung Clearance Index in Cystic Fibrosis—A Pilot Study

Abstract: Background: Life expectancy has increased in cystic fibrosis (CF) patients; however, the rate of mortality is still high, and in a majority of cases, the cause of death is due to respiratory deterioration. Vitamin D plays an important role in immunity and infection prophylaxis, as its deficiency is associated with frequent infections. In CF patients, a deficit of liposoluble vitamins is common, despite daily supplementation. The aim of this study is to evaluate the relation between vitamin D status and lung fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…In a recent systematic review by Iniesta et al, 25-OHD concentration was positively associated with lung function in children and young adults with CF (36). Dediu et al observed that vitamin D deficiency was associated with cystic fibrosis-related diabetes (CFRD), cystic fibrosis liver disease (CFLD), and prolonged lung clearance index in their study (37).…”
Section: Discussionmentioning
confidence: 84%
“…In a recent systematic review by Iniesta et al, 25-OHD concentration was positively associated with lung function in children and young adults with CF (36). Dediu et al observed that vitamin D deficiency was associated with cystic fibrosis-related diabetes (CFRD), cystic fibrosis liver disease (CFLD), and prolonged lung clearance index in their study (37).…”
Section: Discussionmentioning
confidence: 84%
“…In addition, adipose tissue can secrete various inflammatory factors (62), thereby narrowing airway diameter and impairing lung function (63). Notably, being underweight implies compromised nutritional status, which is associated with lung dysfunction (64). Therefore, it is advisable to maintain a normal weight, which is a controllable factor in preventing lung ventilation function impairment.…”
Section: Discussionmentioning
confidence: 99%